1999
DOI: 10.1146/annurev.physiol.61.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Excitation-Contraction Coupling in Gastrointestinal and Other Smooth Muscles

Abstract: The main contributors to increases in [Ca2+]i and tension are the entry of Ca2+ through voltage-dependent channels opened by depolarization or during action potential (AP) or slow-wave discharge, and Ca2+ release from store sites in the cell by the action of IP3 or by Ca(2+)-induced Ca(2+)-release (CICR). The entry of Ca2+ during an AP triggers CICR from up to 20 or more subplasmalemmal store sites (seen as hot spots, using fluorescent indicators); Ca2+ waves then spread from these hot spots, which results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
158
1
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(174 citation statements)
references
References 227 publications
4
158
1
3
Order By: Relevance
“…Similarly, Lee & Wang (1999) reported that fenamates inhibited the voltagedependent K þ channels. The presence of 4-AP-and voltagesensitive K þ currents has been reported in a wide variety of smooth muscle (Bolton et al, 1999). In the present experiments, we were not able to detect the 4-AP-sensitive K þ channels by use of single-channel recordings, and further studies are needed to cast light upon the properties of 4-APsensitive K þ channels in pig urethra.…”
Section: N Teramoto Et Al Effects Of Mefenamic Acid On K þ Currents contrasting
confidence: 64%
“…Similarly, Lee & Wang (1999) reported that fenamates inhibited the voltagedependent K þ channels. The presence of 4-AP-and voltagesensitive K þ currents has been reported in a wide variety of smooth muscle (Bolton et al, 1999). In the present experiments, we were not able to detect the 4-AP-sensitive K þ channels by use of single-channel recordings, and further studies are needed to cast light upon the properties of 4-APsensitive K þ channels in pig urethra.…”
Section: N Teramoto Et Al Effects Of Mefenamic Acid On K þ Currents contrasting
confidence: 64%
“…The initial Ca 2+ mobilization may be augmented by RyR-mediated Ca 2+ release recruited via a CICR mechanism (Bolton and Gordienko, 1998;Bayguinov et al, 2000;White and McGeown, 2002;Kotlikoff, 2003;Zhang et al, 2003;Hotta et al, 2007;Gordienko et al, 2008). The contribution of these mechanisms to intracellular Ca 2+ mobilization may vary in different SMC types, depending on the type and strength of stimuli, SMC excitability and spatial organisation of intracellular Ca 2+ release units (Walsh, 1994;Bolton and Gordienko, 1998;Bolton et al, 1999;Davis and Hill, 1999;Bayguinov et al, 2000;Gordienko et al, 2001Gordienko et al, , 2008Janiak et al, 2001;Gordienko and Bolton, 2002;White and McGeown, 2002;Kotlikoff, 2003;Wier and Morgan, 2003;Zhang et al, 2003;Lamont and Wier, 2004;McCarron et al, 2006;Amberg et al, 2007;Hotta et al, 2007;Wier et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The initial Ca 2+ mobilization may be augmented by RyR-mediated Ca 2+ release recruited via a CICR mechanism (Bolton and Gordienko, 1998;Bayguinov et al, 2000;White and McGeown, 2002;Kotlikoff, 2003;Zhang et al, 2003;Hotta et al, 2007;Gordienko et al, 2008). The contribution of these mechanisms to intracellular Ca 2+ mobilization may vary in different SMC types, depending on the type and strength of stimuli, SMC excitability and spatial organisation of intracellular Ca 2+ release units (Walsh, 1994;Bolton and Gordienko, 1998;Bolton et al, 1999;Davis and Hill, 1999;Bayguinov et al, 2000;Gordienko et al, 2001Gordienko et al, , 2008Janiak et al, 2001;Gordienko and Bolton, 2002;White and McGeown, 2002;Kotlikoff, 2003;Wier and Morgan, 2003;Zhang et al, 2003;Lamont and Wier, 2004;McCarron et al, 2006;Amberg et al, 2007;Hotta et al, 2007;Wier et al, 2009).We hypothesized that in vascular myocytes Ca 2+ entry following activation of ionotropic P2X receptors may induce IP3R-mediated Ca 2+ release. Our hypothesis was based on the following findings reported in visceral and vascular myocytes: (i) a localized increase in [Ca 2+ ]i induced by local flash release of Ca 2+ from a 'caged' precursor may trigger IP3R-mediated Ca 2+ release (Ji et al, 2006); (ii) Ca 2+ entry via VGCCs facilitates IP3R-mediated Ca 2+ release following stimulation of metabotropic receptors (Gordienko et al, 2008); (iii) the stoichiometric ratio of RyRs to IP3Rs in SMCs is 1:9-10, suggesting the existence of a Ca 2+ -storage compartment devoid of RyRs but equipped with IP3Rs (Wibo and Godfraind, 1994); (iv) caffeine/ryanodinereleasable and IP3-releasable calcium stores in the SR of vascular myocytes are at least partially distinct with about 56% of the SR being solely IP3-sensitive (Blauste...…”
mentioning
confidence: 99%
“…2+ levels regulate a plethora of intracellular processes, among them smooth muscle contraction [14] and vascular permeability [15]. The Ca 2+ signals are sensed by calcium-binding proteins, of which calmodulin is the most important.…”
Section: Increased Cytosolic Camentioning
confidence: 99%